Explanations for the Instability of Equity Beta: Risk-Free Rate Changes and Leverage Effects - DeJong, Douglas V.; Collins, Daniel W. (Journal of Financial and Quantitative Analysis, 1985)
Douglas V. DeJong, Daniel W. Collins, Explanations for the Instability of Equity Beta: Risk-Free Rate Changes and Leverage Effects, The Journal of Financial and Quantitative Analysis, Vol. 20, No. 1 (Mar., 1985), pp. 73-94